THE WORD FORMATION PROCESS OF SLANG WORDS IN RICH BRIAN’S SONG TITLED DAT STICK - Teo Mujibul Hidayat; Mu'man Mu'man (PROJECT (Professional Journal of English Education), 2020)
The purposes of this research were to analyze the word formation process of slang words in Dat Stick song. Word formation is a change of words from old form to the new form. This research used descriptive method because the researcher described the word formation process of slang word in the song into the word or sentence in detail. This research used a documentation method to collect the data. The researcher used Yule (2010) theory to analyze the slang word. There are 10 types of word formation process which consist of coinage, borrowing, compounding, blending, clipping, and back-formation, conversion, acronym, derivation, and multiple process. Based on these 10 types, the researcher found 5 type of words formation process of 16 slang words. There were 9 from the clipping process, 1 from multiple process, 3 from acronym process, 1 from coinage process and 2 from blending process. Based on the results above, the most formed words were the clipping process. Keywords:  Word formation, Slang words, Song